Transport and retention of graphene oxide nanoparticles in sandy and carbonaceous aquifer sediments: Effect of physicochemical factors and natural biofilm. (15th January 2021) - Ramazanpour Esfahani, Amirhosein; Batelaan, Okke; Hutson, John L.; Fallowfield, Howard J.
Abstract: There is a paucity of information regarding the interaction between GONPs and natural aquifer sediments. Therefore, batch and column experiments were carried out to determine the transport, retention and attachment behavior of GONPs with the surfaces of native aquifer sediments. The experiments were performed with sediments comprising contrasting mineralogical features (sand grains, quartz and limestone sediments), at different temperatures, ionic strength and compositions. Uniquely, this research also investigated the effect of natural biofilm on the retention behavior of nanoparticles in porous media. The retention rate of GONPs at 22 °C was higher than at 4 °C. Moreover, there was greater retention of GONPs onto the surfaces of collectors at higher ionic strengths and cation valence. The retention profiles (RPs) of GONPs in pristine porous media at low ionic strength were linear, which contrasted with hyper-exponential shape of RPs at high ionic strength. The size-distribution analysis of retained GONPs showed decreasing particle diameter with increasing distance from the column inlet at high ionic strength and equal diameter at low ionic strengths. The GONP retention rate was higher for natural porous media than for sand, due to the presence of metal oxides heterogeneities. The presence of biofilm on porous media increased the retention rate of GONPs when compared to the porous media in the absence of biofilm. Graphical abstract: Image 1 Highlights: High retention of GONPs was observed in natural sediments containing metal oxides. Increasing temperature enhances GONP attachment and retention in porous media. Biofilms act as a biofilter against transport of nanoparticles in porous media.